Fish of Ara-Nur Lake (Transbaikal region) - E.P. Gorlacheva (Acta Biologica Sibirica, 2019)
We presented the list of fish species founded in the Lake Ara-Nur in 1998-1999. These data has not been published previously and no research was carried out in the lake since this study. The fish fauna included 11 species belonged to 7 families. The lake and basin of the River Khilok had low species diversity. Freshwater fish species of the boreal lowland were dominant in Ara-Nur fauna. Along with the limnetic fish species, we registered some fluvial fish species entered into the lake from the Northern Gorek River. Most of the fish are benthophage, the others are ichthyophagous and euryphagous; the majority of species are limnophylics. In our opinion, Lake Ara-Nur has great potential importance for fish spawning and wintering